DEXAMETHASONE FOR THIRD MOLAR SURGERY- A REVIEW - PRAKASH DHANAVELU,; SHANMUGAPRIYAN,; VIJAY EBENEZER,; BALAKRISHNAN,; M ELUMALAI, (International Journal of Pharma and Bio Sciences, 2013)
Every oral surgeon has encountered problems associated with edema, trismus, and pain after third Molar surgeries. In third-molar surgery, fear of pain and trismus are often directly proportional to edema. Use of the corticosteroid, dexamethasone, given as intramuscular, intravenous or sub mucosal either as preoperative, perioperative or postoperative injection , appears to be effective in the prevention of postoperative edema. This article reviews about the best technique and the dose required to minimize patient discomfort in third molar surgery.